(untitled) (Journal of Advanced Veterinary and Animal Research, 2015)
The study was carried out to investigate the associated maggots and bacteria in myiasis affected wound in animals. Total 37 myiasis affected cattle (n=25) and goats (n=12) were examined in this study, of which 21 samples were collected from the Veterinary clinics of Bangladesh Agricultural University (BAU), Mymensingh, and the remaining 16 samples were collected from Upazila Veterinary Hospital, Gouripur, Mymensingh. The maggots were collected from the wounds, and were identified under microscope. For microbial identification, samples (n=10) were collected aseptically by using sterile cotton swab. The samples were allowed to grow in media. Colony and staining characteristics were studied. Traumatic, creeping or migratory myiasis wounds were identified in the examined animals. In this study, subcutaneous wound was mostly recorded, of which 43% (n=9/21) was found at the Veterinary Clinics, BAU, and 44% (n=7/16) was found at the Upazila Veterinary Hospital, Gouripur. The maggots were identified as Chrysomya bezziana, commonly known as Old World screwworm. Occurrence of myiasis due to C. bezziana larvae was recorded as 100%. The associated bacteria were identified as Staphylococcus spp. In conclusion, the myiasis wounds are associated with both Staphylococcus spp. and larvae of C. bezziana. Preventive and control measures against the C. bezziana and Staphylococcus spp. can be undertaken to save the livestock from myiasis in Bangladesh. DOI: http://dx.doi.org/10.5455/javar.2015.b55